2021
DOI: 10.1186/s12913-021-06859-6
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative assessment of barriers and facilitators associated with addressing social determinants of health among members of a health collaborative in the rural Midwest

Abstract: Purpose Rural communities have unique economic and social structures, different disease burdens, and a more patchworked healthcare delivery system compared to urban counterparts. Yet research into addressing social determinants of health has focused on larger, urban, integrated health systems. Our study sought to understand capacities, facilitators, and barriers related to addressing social health needs across a collaborative of independent provider organizations in rural Northeastern Minnesota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 26 publications
2
32
0
Order By: Relevance
“…Data from the current study revealed a negative gradient from the patient level to the community level in terms of integration of social determinants into clinical practice, thus highlighting deficiencies in macro-level actions for integration of social determinants into clinical practice. The gradient was like what was observed among members of a health collaborative in rural Northeastern Minnesota and Northwestern Wisconsin [27].…”
Section: Discussionsupporting
confidence: 59%
“…Data from the current study revealed a negative gradient from the patient level to the community level in terms of integration of social determinants into clinical practice, thus highlighting deficiencies in macro-level actions for integration of social determinants into clinical practice. The gradient was like what was observed among members of a health collaborative in rural Northeastern Minnesota and Northwestern Wisconsin [27].…”
Section: Discussionsupporting
confidence: 59%
“…The others were not knowing the actions to undertake after identifying social factors [15], deficiencies in community social services and limitation in community-based resources. Some of the barriers highlighted in literature such as lack of a systematic screening process, lack of organized internal and external advocacy regarding the value of integration of social determinants into clinical practice, inappropriate payer policies, and misaligned incentives [22] and bias towards the medical model and treatment imperative, prior experiences of stereotypes and discrimination, physical fatigue [15] were not observed in this study. This difference is attributed to the difference in study setting and tools used.…”
Section: Discussionmentioning
confidence: 78%
“…A qualitative study conducted by Dauner et al found that community health workers reported areas where resource shortages existed included the need for mental health clinicians; transportation; Internet; long-term care including memory care, respite, personal care services and hospice; specialty care; emergency medical services; public health department staffing; general workforce; and housing, specifically Section 8 housing [58]. Due to these shortages, their ability to address social determinants of health was very limited [58]. Resources such as transportation assistance was limited due to a complete lack of staff to assist or the inability for the healthcare worker themselves to participate due to legal hurdles.…”
Section: Rural Health Resource Disparitiesmentioning
confidence: 99%
“…Partner capacity appeared to be another challenge when addressing the needs of rural communities. Because social service partners did not have the capacity to take on more work, lower socioeconomic and less densely populated communities were adversely affected [58]. It was noted that in the wake of COVID-19, while some community partners noticed more engagement between each other, others stated that the pandemic exacerbated their internal issues and they struggled to stay aware of all the resources available between agencies [58].…”
Section: Rural Health Resource Disparitiesmentioning
confidence: 99%